2020
DOI: 10.3390/pharmaceutics13010021
|View full text |Cite
|
Sign up to set email alerts
|

Medication Safety in Intravenous Therapy: A Compatibility Study of Clonidine with Drugs Frequently Used in Intensive Care

Abstract: The intravenous pharmacotherapy of critically ill patients is extremely challenging due to the high number of drugs administered. We therefore evaluated the physicochemical compatibility of combinations of clonidine with drugs frequently used in an intensive care unit setting. Amiodarone, dihydralazine, furosemide, levosimendan, metamizole, milrinone, urapidil, and verapamil were each prepared as binary combinations with clonidine at the standard low and high administration concentrations. Selected ternary com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The ratio of the mean peak areas was determined and the 95% CI of the ratio was calculated using the confidence limits from a two-sided t -test (α = 0.05; SigmaPlot V.15; Inpixon GmbH, Düsseldorf, Germany). Consistent with previous studies, incompatibilities of sildenafil:drug combinations were defined as a ratio of the mean peak area outside the range of 90–110% [ 8 , 9 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of the mean peak areas was determined and the 95% CI of the ratio was calculated using the confidence limits from a two-sided t -test (α = 0.05; SigmaPlot V.15; Inpixon GmbH, Düsseldorf, Germany). Consistent with previous studies, incompatibilities of sildenafil:drug combinations were defined as a ratio of the mean peak area outside the range of 90–110% [ 8 , 9 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the chemical stability of drugs for infusion, in our case after co-administration via the same port, has been studied using quantitative methods like high-performance liquid chromatography, while physical compatibility (e.g., precipitation, color change, and oil droplet growth in an emulsion) frequently was relying on visual observations, aided by microscopy or Tyndall beam. These approaches have methodological and practical shortcomings not least when combinations of three or more drugs are of interest. Developing validated methods for multiple component solutions demands time and resources, and relying on visual control for detection of precipitates does not cover sub-visible particles neither does it provide the solid form identity of the precipitate.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the chemical stability of drugs for infusion, in our case after co-administration via the same port, has been studied using quantitative methods like high-performance liquid chromatography, 9 13 while physical compatibility (e.g., precipitation, color change, and oil droplet growth in an emulsion) frequently was relying on visual observations, aided by microscopy or Tyndall beam. 14 16 These approaches have methodological and practical shortcomings not least when combinations of three or more drugs are of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Turbidity and pH measurements are commonly conducted in physical compatibility studies and have been reported in physicochemical compatibility investigations. 7 , 8 , 9 , 10 , 11 However, there are resource implications for these tests, not least the requirement for large sample volumes (typically > 10 ml), which is problematic for expensive drugs. Furthermore, the intrinsic value of some physical compatibility tests is unclear and interpretation or specification limits may be inconsistent 12 ; for example, in regard to pH unit shift.…”
mentioning
confidence: 99%
“…Furthermore, the intrinsic value of some physical compatibility tests is unclear and interpretation or specification limits may be inconsistent 12 ; for example, in regard to pH unit shift. 9 , 10 , 11 In regard to quantifying only the PTX concentration, we have assumed that physicochemical incompatibility would be the result of interaction between the two drugs and should be detected by the HPLC assay of the primary drug. Although there may be value in quantifying the secondary drug if chemical incompatibility is detected or suspected, a significant impediment to quantifying all of the secondary drugs would be developing and validating HPLC assays for the full range of drugs.…”
mentioning
confidence: 99%